THE ESSENCE OF THE CHURCH AND ITS PRESENCE FOR SOCIETAL TRANSFORMATION - Mawikere, Marde Christian Stenly; Hura, Sudiria; Mawikere, Jean Calvin Riedel; Mawikere, Daniella Beauty Melanesia (PT. Giat Konseling Nusantara, 2024)
This study delves into the pivotal role of the church as an agent of social transformation, emphasizing its significant contributions to fostering holistic and sustainable changes within society. Employing a qualitative approach, the research undertakes an in-depth exploration and analysis of the church's role through an extensive literature review. Through meticulous content analysis, the study uncovers recurring patterns in relevant literature, elucidating how the church exerts its influence on social change through active participation, empowerment initiatives, and the cultivation of meaningful community relationships. Moreover, the study underscores the paramount importance of contextualizing church ministry within the local culture and advocating for pertinent spiritual values. By centering on the church’s impact on societal transformation, this research offers profound insights into its role as a comprehensive catalyst for change, emphasizing the church's inherent responsibility in fostering enhanced community well-being.